Análisis de los restos óseos recuperados en el rescate arqueológico del cementerio Central (Montevideo, Uruguay) - Rojo, Belén (2021)
In January 2019 there was a partial collapse of the «E» wing of the first body of funerary niches of the Central Cemetery of Montevideo, affecting 64 niches containing burials from the mid-nineteenth century to the present. The archaeological rescue work of the collapsed sector resulted in the recovery of intact or slightly altered funerary structures and in the extraction of displaced or isolated remains that were analyzed separately and are the object of this work. The remains were studied in order to determine the number of individuals, sex and age structure, and the effect of the collapse and the recovery methodology on the representation of bone elements. Three specific studies were carried out on subsets of the sample: taphonomy of adult individuals, age and sex structure of subadults, and osteobiography of two individuals. Although the inferences made should be taken with caution due to the fragmentary nature of the analyzed remains, it is concluded that the remains have an important potential as a source of knowledge of postdepositional factors, demography and living conditions of the high socio-economic status population of the city of Montevideo in the second half of the 19th century and first half of the 20th century.